Aplikasi Pembelajaran Sistem Pendukung Keputusan Menggunakan Metode Weighted Product - Yunus, Mughaffir; Sahidin, Sudirman; Rafly Arifin, Mohammed (Jurnal Sintaks Logika, 2025)
tudents can develop creativity, insight, and mindset by following the trend of learning media that utilizes technology using learning media applications. The purpose of this study is to create a learning application to help students understand the concept of decision support systems. This study uses quantitative methodology based on literature studies with the weighted product method. The results of the study show that this learning application can be used by students in studying the Weighted Product Method Decision Support System, both in theory and practice. The Weighted Product method can help in making decisions with the greatest value that will be selected as the best alternative. The test results with 3 SPKs can be seen from the accuracy of the calculation of the weighted product method application which can provide accurate results in finding the best alternative decision ranking.